Tripod Fracture in Adolescent: A Case Report - I Gusti Ayu Agung Bella Jayaningrum (Utan Kayu Publishing, 2021)
Fractures that accompany the zygomatic complex can cause complications such as dystopia, enophthalmos and aesthetic changes if not treated in a timely manner. Current treatments rely on material and diagnostic resources, such as CT scans, to provide excellent aesthetic and functional results. The objective of this work is to present a case of orbital floor fracture and lateral wall of left orbit, showing aesthetic and functional results. We present a case from a 17 years old, male patient who fell from the roof with his face hitting the floor for the first time. Based on clinical and supportive examination, diagnosis of tripod fracture was made. Open reduction with internal fixation with miniplates and screws was performed to this patient.